Factors affecting the Academic performance of BSCA students in Gordon College - Haniba, Crystal Anne; Garin, Elvis Lorence; Jimenez, Ar-Jhay; Gutierrez, Janus Vincent; Frondozo, Ericka Faye; Malong, Sherinne Angel; Paras, Patricia Anne; Del Rosario, Leo; Nicdao, Rochelle Shiana; Miguel, Michael John (Asian Journal of Applied Education (AJAE), 2025)
The research investigated factors influencing the academic performance of Bachelor of Science in Customs Administration (BSCA) students at Gordon College. One hundred twenty 2nd - 4th year students participated in a descriptive survey using questionnaires. Analysis methods included weighted mean, and structural equation modeling. Results highlighted that academic performance clustered around grades 85-89, indicating solid achievement. Influential factors included personal conditions, study habits, and home and school environments, with study habits notably critical. Lecturer and technological factors had minimal impact. Overall, the study underscored a positive academic setting and substantial student achievement.